Age-Dependent Targeting of Protein Phosphatase 1 to Ca2+/Calmodulin-Dependent Protein Kinase II by Spinophilin in Mouse Striatum - Baucum, II, Anthony J.; Strack, Stefan; Colbran, Roger J. (PLOS ONE, 2012)
Mechanisms underlying age-dependent changes of dendritic spines on striatal medium spiny neurons are poorly understood. Spinophilin is an F-actin- and protein phosphatase 1 (PP1)-binding protein that targets PP1 to multiple downstream effectors to modulate dendritic spine morphology and function. We found that calcium/calmodulin-dependent protein kinase II (CaMKII) directly and indirectly associates with N- and C-terminal domains of spinophilin, but F-actin can displace CaMKII from the N-terminal domain. Spinophilin co-localizes PP1 with CaMKII on the F-actin cytoskeleton in heterologous cells, and spinophilin co-localizes with synaptic CaMKII in neuronal cultures. Thr286 autophosphorylation enhances the binding of CaMKII to spinophilin in vitro and in vivo. Although there is no change in total levels of Thr286 autophosphorylation, maturation from postnatal day 21 into adulthood robustly enhances the levels of CaMKII that co-immunoprecipitate with spinophilin from mouse striatal extracts. Moreover, N- and C-terminal domain fragments of spinophilin bind more CaMKII from adult vs. postnatal day 21 striatal lysates. Total levels of other proteins that interact with C-terminal domains of spinophilin decrease during maturation, perhaps reducing competition for CaMKII binding to the C-terminal domain. In contrast, total levels of α-internexin and binding of α-internexin to the spinophilin N-terminal domain increases with maturation, perhaps bridging an indirect interaction with CaMKII. Moreover, there is an increase in the levels of myosin Va, α-internexin, spinophilin, and PP1 in striatal CaMKII immune complexes isolated from adult and aged mice compared to those from postnatal day 21. These changes in spinophilin/CaMKII interactomes may contribute to changes in striatal dendritic spine density, morphology, and function during normal postnatal maturation and aging.